2010
DOI: 10.1016/j.stem.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the HIF-1α Level Is Essential for Hematopoietic Stem Cells

Abstract: Hematopoietic stem cells (HSCs) are sustained in a specific microenvironment known as the stem cell niche. Mammalian HSCs are kept quiescent in the endosteal niche, a hypoxic zone of the bone marrow (BM). In this study, we show that normal HSCs maintain intracellular hypoxia and stabilize hypoxia-inducible factor-1alpha (HIF-1alpha) protein. In HIF-1alpha-deficient mice, the HSCs lost their cell cycle quiescence and HSC numbers decreased during various stress settings including bone marrow transplantation, mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
809
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 806 publications
(849 citation statements)
references
References 40 publications
37
809
2
1
Order By: Relevance
“…HIF activation by hypoxic niches within bone marrow is critically important for controlling the fate of hematopoietic stem cells and their progeny, orchestrating a balance of quiescence, self-renewal, differentiation, and apoptosis (37,38). Because TACC3-/-embryos exhibit dramatically reduced hematopoietic stem cell colony formation activity (approximately 1-5% of WT) (30), we propose that loss of TACC3 may compromise HIF activity and regulation of hematopoietic stem cell fate.…”
Section: Mutations In Arnt Pas-b Perturb Coactivator Binding and Hifmentioning
confidence: 99%
“…HIF activation by hypoxic niches within bone marrow is critically important for controlling the fate of hematopoietic stem cells and their progeny, orchestrating a balance of quiescence, self-renewal, differentiation, and apoptosis (37,38). Because TACC3-/-embryos exhibit dramatically reduced hematopoietic stem cell colony formation activity (approximately 1-5% of WT) (30), we propose that loss of TACC3 may compromise HIF activity and regulation of hematopoietic stem cell fate.…”
Section: Mutations In Arnt Pas-b Perturb Coactivator Binding and Hifmentioning
confidence: 99%
“…Recently, Takubo et al (35) reported that normal hematopoietic stem cells (HSCs) maintain intracellular hypoxia and stabilize HIF-1␣ protein and that HSCs maintain cell cycle quiescence through the precise regulation of the HIF-1␣ level. It was also shown that HIF-1␣ plays a role in myeloid leukemic cell differentiation induced by hypoxia (14, 28, 36 -38) and that a clinically useful differentiation-inducing drug, all-trans retinoic acid, stabilizes HIF-1␣ protein (30).…”
Section: Ttgcaatmentioning
confidence: 99%
“…This effect has been shown to be dependent on HIF-1α in multiple cell types, including various cancer cell lines (31)(32)(33)(34), fibroblasts (34), lymphocytes (34), and hematopoietic stem cells (35). Forced overexpression of HIF-1α is sufficient to arrest the mammalian cell cycle in G1 phase (31,36).…”
mentioning
confidence: 99%